2019
DOI: 10.1021/acs.iecr.8b05815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Nanotube and Carbon Sphere Templates in TiO2 Composites for Photocatalytic Hydrogen Production

Abstract: Incorporation of carbonaceous templates (CT) into TiO2 composites is a promising alternative to increase the photocatalytic activity of TiO2. In this work, the effects of carbon sphere (CS) and carbon nanotube (CNT) incorporation (as CT) in TiO2 composites were thoroughly investigated and the roles of these CTs as template, cocatalyst, and adsorbent were studied. To this end, three different methods were utilized to form a layer of TiO2 on the CT: alcoholic phase sol–gel, aqueous phase sol–gel, and hydrotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Carbonaceous TiO 2 composites with carbon templates (carbon sphere and CNT) as a co‐catalyst have been prepared using various synthesis methods (hydrothermal, aqueous phase sol‐gel, and alcohol phase sol‐gel) at various calcination temperatures (300‐800°C). TiO 2 @CNT prepared via the aqueous sol‐gel method at 400°C has the highest hydrogen production activity among those prepared at other temperatures 118 . Multi‐walled CNTs (MWCNTs)/TiO 2 nanocomposites were successfully prepared using a hydrothermal method with different weight percentages of MWCNTs (0, 0.05, 0.1, and 0.5 wt%) 117 .…”
Section: Co‐catalysts On Metal Oxides For Photocatalytic Hydrogen Gen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonaceous TiO 2 composites with carbon templates (carbon sphere and CNT) as a co‐catalyst have been prepared using various synthesis methods (hydrothermal, aqueous phase sol‐gel, and alcohol phase sol‐gel) at various calcination temperatures (300‐800°C). TiO 2 @CNT prepared via the aqueous sol‐gel method at 400°C has the highest hydrogen production activity among those prepared at other temperatures 118 . Multi‐walled CNTs (MWCNTs)/TiO 2 nanocomposites were successfully prepared using a hydrothermal method with different weight percentages of MWCNTs (0, 0.05, 0.1, and 0.5 wt%) 117 .…”
Section: Co‐catalysts On Metal Oxides For Photocatalytic Hydrogen Gen...mentioning
confidence: 99%
“…In fact, the existence of CNTs in the TiO 2 composite as a co‐catalyst, sensitizer, or both is highly effective for H 2 production because the CB edge of CNTs is lower than that of TiO 2 . Hence, the photogenerated electrons are easily transferred during the reaction 117,118 …”
Section: Co‐catalysts On Metal Oxides For Photocatalytic Hydrogen Gen...mentioning
confidence: 99%
“…It was reported that only 0.05 wt % Pt on TiO 2 as a cocatalyst can increase the rate of glycerol transformation into hydrogen around 370 times . Although Pt is the most common cocatalyst for hydrogen production from glycerol, ,,,,,,, , ,,,,, other metals like Cu, ,,,,,,,,,,,,, Au, ,,,,,, Pd, ,,,,, Ni, ,,,,, Co, ,, Ag, ,, Mn, Ru, Rh, Bi, , Cr, , and W have also been employed as cocatalysts to enhance the TiO 2 photocatalytic activity.…”
Section: Photocatalyst Development For Glycerol Valorizationmentioning
confidence: 99%
“…In the resulting equation (Equation 13), the reaction rates with respect to the concentration of adsorbed species are shown as mth and nth orders. It is worth mentioning that Reactions (6) and 7may not be elementary as they can follow different pathways and steps. In these reactions, the proton is first trapped by the substrate or water, and then a H + is released.…”
Section: The Oxidation Reaction Occurs On the Surface Of Semiconductormentioning
confidence: 99%
“…Renewable hydrogen is considered as a promising energy source of the future . Different techniques such as thermal, biological, photoelectrochemical, and photocatalytic can be followed for hydrogen production. Photoelectrochemical and photocatalytic techniques take advantage of utilizing renewable solar energy, and operating at ambient temperature and atmospheric pressure .…”
Section: Introductionmentioning
confidence: 99%